Protective Effect of Vitis gracilis Wall (Vitaceae) Leaf Decoction on Sexual Vitality and Testis of Alloxan-Induced Diabetic Mice - Putra Santoso; Syafruddin Ilyas; Yurnadi Hanafi Midoen; Alfi Yuniarti (Tehran University of Medical Sciences, 2023)
Diabetes mellitus is profoundly associated with various detrimental outcomes including sexual dysfunction and infertility in males. On the other hand, a medicinal plant namely Vitis gracilis Wall (Vitaceae) has been used as a traditional medicine to enhance vitality. This present study aimed to investigate the protective effect of V. gracilis leaf decoction against diabetes-induced sexual dysfunction and testicle histopathology in adult male mice. The experiment was composed of five different groups namely the control (non-diabetic) group, the diabetes group (without any treatments), and the diabetes treated with V.gracilis decoction at the doses of 25, 50, and 100 g/ L, respectively. In addition, the phytochemical constituents of leaf decoction were determined by using Ultra performance-liquid chromatography-mass spectroscopy (UPLC-MS). Our data demonstrated that, despite failing to improve blood glucose profile and body weight, V.gracilis leaf decoction sustained intense sexual behaviors including face and genital kissing, genital licking, and mount toward estrous females. Moreover, lower doses of decoction (25 and 50 g/ L) attenuated the diabetes-induced reduction of testis weight and precluded malondialdehyde accumulation in the testicle tissue. The decoction at the lower doses also ameliorated histopathological alterations in the testis, particularly the wall thickness of tubulus seminiferous and the number of necrotic cells. V. gracilis decoction also improved hematological values including hemoglobin (Hb), red blood cell count and hematocrit (HTC) level. In addition, UPLC-MS analysis revealed a total of 26 phytochemical compounds with seven predominant substances. In conclusion, leaf decoction of V. gracilis, particularly at lower doses but not at a higher dose, exerted a protective effect on sexual vitality, testicle tissue, and hematological value under diabetic condition. The beneficial effects of V.gracilis decoction might be associated with its various bioactive compounds. Therefore, V. gracilis leaves may be a future candidate as a potent natural drug for male sexual vitality and testicle protection against diabetes.